Cross-cultural messaging: Evaluating the consistency of climate change communication post-translation - Ratna Maharani Patria; Saputri Lenggahing Asri Dwi Eko; Zunaira Rubi Yoshiko; Ghifara Misykah Auliya (E3S Web of Conferences)
This study investigates cross-cultural message consistency in climate change communication by evaluating the translation techniques used in environmental campaigns translated from English to Japanese. Using a qualitative approach, this study analyzes the translated environmental campaign materials, focusing on the identification and analysis of translation techniques used to translate messages or slogans. The analysis draws on an existing taxonomy of translation techniques to categorize and examine the strategies used by translators. The findings show that calque (kalki) is the most frequently used translation technique, followed by modulation. This indicates a tendency to prioritize closeness to the meaning and structure of the source text as well as ensuring naturalness in the target language. Other techniques, such as transposition, amplification and adaptation, were used less frequently. This study contributes to the understanding of cross-cultural messages in environmental campaigns and highlights the importance of translators’ decisions in maintaining consistency of messages across languages and cultures.